2020
DOI: 10.1007/s00540-020-02821-8
|View full text |Cite
|
Sign up to set email alerts
|

Tapentadol is effective in the management of moderate-to-severe cancer-related pain in opioid-naïve and opioid-tolerant patients: a retrospective study

Abstract: Purpose Tapentadol is a dual-acting mu-opioid receptor agonist and noradrenaline reuptake inhibitor with non-inferior analgesic efficacy to oxycodone and better gastrointestinal tolerability than full mu-opioid receptor agonists. Tapentadol is approved for cancer pain in Japan; however, real-world evidence on tapentadol’s effectiveness and safety for cancer-related pain in Japan is limited. Methods This retrospective study evaluated the effectiveness, safety, and tolerability of tapentadol (by patient type—op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, three opioidtolerant patients experienced tapentadol-related nausea. There were no discontinuations due to serious adverse events [29].…”
Section: Nonrandomized Studies Of Tapentadol In Patients With Cancer ...mentioning
confidence: 91%
See 1 more Smart Citation
“…However, three opioidtolerant patients experienced tapentadol-related nausea. There were no discontinuations due to serious adverse events [29].…”
Section: Nonrandomized Studies Of Tapentadol In Patients With Cancer ...mentioning
confidence: 91%
“…A retrospective single-center study in 84 Japanese patients with moderate to severe cancer pain evaluated the effectiveness, safety, and tolerability of tapentadol [29]. 93% greater than or equal to 50% reduction in NRS score from baseline.…”
Section: Nonrandomized Studies Of Tapentadol In Patients With Cancer ...mentioning
confidence: 99%
“…However, to date, there is still only modest evidence about the effectiveness of tramadol in NCP [54]. Tapentadol is a dual-acting µ-opioid receptor agonist and noradrenaline reuptake inhibitor, and its use has been suggested also for NCP, especially for cases in which an immediate dose adjustment is required or in patients at high risk for adverse effects [55,56].…”
Section: Opioidsmentioning
confidence: 99%
“…Studies have shown it is effective in managing moderate–severe cancer pain; in an observational prospective study, 88% ( n = 80) were classed as responders maintaining a score on a numerical rating scale (NRS) of 3 or less with significant improvements seen in pain intensity ( P < 0.01) and neuropathic pain ( P < 0.01) [15]. A 2020 retrospective single centre study in moderate-to-severe cancer pain ( n = 84) found clinically relevant pain relief demonstrated by a 50% reduction in NRS was achieved in both opioid-tolerant and opioid-naïve patients (94.5 and 89.7%, respectively) within a median of 3 days [16 ▪ ].…”
Section: Tapentadolmentioning
confidence: 99%